THE LEADERSHIP OF HUMAN RESOURCE TRAINING AND THEIR IMPACT ON ORGANISATIONAL PERFORMANCE - Ariana Xhemajli; Brikenda Vokshi; Emin Neziraj (Human Research in Rehabilitation, 2022)
The aims of this paper are to contribute to the deepening of research in this field in SEE countries, but also the application of appropriate knowledge in organizations, to increase performance, improve organizational culture, strengthen leadership of human resource management. The paper examines the factors that affect employee motivation and encourages the understanding that continuous improvement of knowledge can achieve high results that would reflect on their professional success and personal needs, as well as on the business of the organization. The paper is realized in accordance with the contemporary principles of scientific-research work. In the analysis, special attention was paid to the works and attitude research results show a significant positive correlation between attitude towards company goals and attitude towards leading training, as well as development of human resource function and attitude towards training.